Body mass index, sleep quality, stress conditions determine menstrual cycles among female adolescents - Rosmauli Jerimia Fitriani; Ari Probandari; Budiyanti Wiboworini (Intelektual Pustaka Media Utama, 2019)
Menstrual cycles are an important indicator of women's health. Menstrual cycles can be affected by body mass index (BMI), sleep quality, and stress. This study aimed to analyse the relationship between BMI, sleep quality, stress and the menstrual cycle. The subjects of this research were the female adolescents at the age of at least 15 years old that had experienced menstruation for at least 2 years. The dependent variable is the menstrual cycle while the independent variables are BMI, sleep quality, and stress conditions. Observational analytic research method with Cross sectional design was used in this research. The subjects were 148 female students. The BMI data were obtained through the anthropometric measurement. The sleep quality data were taken with PSQI questionnaire, and the stress condition data obtained from PSS-10 questionnaire which were then analysed using Chi-Square test and Logistic Regression. Results of study showed that there is a significant relationship between BMI, sleep quality, stress conditions and the adolescent menstrual cycle. The results of the multivariate analysis showed that the female adolescents with abnormal BMI are at risk of having menstrual cycle disorders 1.91 times. The adolescents with poor sleep quality are at risk experiencing menstrual cycle disorders 2.05 times, and the adolescents with stress conditions at risk of the menstrual cycle disorders 2.26 times. There is a relationship between BMI, sleep quality, stress conditions and the menstrual cycle. Stress conditions most influence the regularity of the menstrual cycle.